Aktuelle Registerstudien beim akuten ischämischen Schlaganfall - Veltkamp, Roland; Purrucker, Jan; Ringleb, Peter A. (Der Nervenarzt, 2012)
SummaryStudy registries offer the opportunity to evaluate the effects of new therapies or to observe the consequences of new treatments in clinical practice. The SITS-MOST registry confirmed the validity of findings from randomized trials on intravenous thrombolysis concerning safety and efficacy in the clinical routine. Current study registries concerning new interventional thrombectomy techniques suggest a high recanalization rate; however, the clinical benefit can only be evaluated in randomized, controlled trials. Similarly, the experiences of the BASICS registry on basilar artery occlusion have led to the initiation of a controlled trial. The benefit of hemicraniectomy in malignant middle cerebral artery infarction has been demonstrated by the pooled analysis of three randomized trials. Numerous relevant aspects are currently documented in the DESTINY-R registry. Finally, the recently started RASUNOA registry examines diagnostic and therapeutic aspects of ischemic and hemorrhagic stroke occurring during therapy with new oral anticoagulants.